Transport-related measures to mitigate climate change in Basel, Switzerland: A health-effectiveness comparison study. (December 2015) - Perez, L.; Trüeb, S.; Cowie, H.; Keuken, M.P.; Mudu, P.; Ragettli, M.S.; Sarigiannis, D.A.; Tobollik, M.; Tuomisto, J.; Vienneau, D.; Sabel, C.; Künzli, N.
Abstract: Background: Local strategies to reduce green-house gases (GHG) imply changes of non-climatic exposure patterns. Objective: To assess the health impacts of locally relevant transport-related climate change policies in Basel, Switzerland. Methods: We modelled change in mortality and morbidity for the year 2020 based on several locally relevant transport scenarios including all decided transport policies up to 2020, additional realistic and hypothesized traffic reductions, as well as ambitious diffusion levels of electric cars. The scenarios were compared to the reference condition in 2010 assumed as status quo. The changes in non-climatic population exposure included ambient air pollution, physical activity, and noise. As secondary outcome, changes in Disability-Adjusted Life Years (DALYs) were put into perspective with predicted changes of CO2 emissions and fuel consumption. Results: Under the scenario that assumed a strict particle emissions standard in diesel cars and all planned transport measures, 3% of premature deaths could be prevented from projected PM2.5 exposure reduction. A traffic reduction scenario assuming more active trips provided only minor added health benefits for any of the changes in exposure considered. A hypothetical strong support to electric vehicles diffusion would have the largest health effectiveness given that the energy production in Basel comes from renewable sources. Conclusion: The planned local transport related GHG emission reduction policies in Basel are sensible for mitigating climate change and improving public health. In this context, the most effective policy remains increasing zero-emission vehicles. Highlights: Local strategies to reduce green-house gases (GHG) imply changes of other non-climatic exposure patterns. To what extent local actions can really contribute to mitigation of climate change impacts given other local needs, priorities and realities is still unknown. We modelled changes in mortality and morbidity in Basel for the year 2020 for different urban Scenarios. We found that the most effective policy at reducing GHG emissions remains increasing zero-emission vehicles at levels beyond the control of local authorities. Local measures that encourage public and active transport are the most effective at both reducing GHG emissions and improving health.